Heterothermy as the Norm, Homeothermy as the Exception: Variable Torpor Patterns in the South American Marsupial Monito del Monte (Dromiciops gliroides) - Nespolo, Roberto F.; Mejías, Carlos; Espinoza, Angelo; Quintero-Galvis, Julián; Rezende, Enrico L.; Fontúrbel, Francisco E.; Bozinovic, Francisco (Frontiers in Physiology, 2021)
Hibernation (i.e., multiday torpor) is considered an adaptive strategy of mammals to face seasonal environmental challenges such as food, cold, and/or water shortage. It has been considered functionally different from daily torpor, a physiological strategy to cope with unpredictable environments. However, recent studies have shown large variability in patterns of hibernation and daily torpor (“heterothermic responses”), especially in species from tropical and subtropical regions. The arboreal marsupial “monito del monte” (Dromiciops gliroides) is the last living representative of the order Microbiotheria and is known to express both short torpor episodes and also multiday torpor depending on environmental conditions. However, only limited laboratory experiments have documented these patterns in D. gliroides. Here, we combined laboratory and field experiments to characterize the heterothermic responses in this marsupial at extreme temperatures. We used intraperitoneal data loggers and simultaneous measurement of ambient and body temperatures (TA and TB, respectively) for analyzing variations in the thermal differential, in active and torpid animals. We also explored how this differential was affected by environmental variables (TA, natural photoperiod changes, food availability, and body mass changes), using mixed-effects generalized linear models. Our results suggest that: (1) individuals express short bouts of torpor, independently of TA and even during the reproductive period; (2) seasonal torpor also occurs in D. gliroides, with a maximum bout duration of 5 days and a mean defended TB of 3.6 ± 0.9°C (one individual controlled TB at 0.09°C, at sub-freezing TA); (3) the best model explaining torpor occurrence (Akaike information criteria weight = 0.59) discarded all predictor variables except for photoperiod and a photoperiod by food interaction. Altogether, these results confirm that this marsupial expresses a dynamic form of torpor that progresses from short torpor to hibernation as daylength shortens. These data add to a growing body of evidence characterizing tropical and sub-tropical heterothermy as a form of opportunistic torpor, expressed as daily or seasonal torpor depending on environmental conditions.